NANOSTRUCTURE LIPID CARRIERS: A PROMISING TOOL FOR THE DRUG DELIVERY IN THE TREATMENT OF SKIN CANCERNANOSTRUCTURE LIPID CARRIERS: A PROMISING TOOL FOR THE DRUG DELIVERY IN THE TREATMENT OF SKIN CANCER - ARTI MAJUMDAR,; NIDHI DUBEY,; NEELESH MALVIYA, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Skin cancer is the most common type of cancer having a very high rate of incidence, exceeding the sum of all other types of cancers. Current topical treatments for non-melanoma skin cancer and their precursor lesions, such as actinic keratosis includes conventional treatments using semisolid formulations of 5-fluorouracil, diclofenac, and imiquimod. Photodynamic therapy is another topical treatment which is used and approved by the US Food and Drug Administration. However, these conventional treatments present various side effects such as severe inflammation, pain, long duration of treatment, and unappealing scars leading to noncompliance of the patients. Hence, the main objective of this review is to highlight the advantages of nanostructured lipid carriers (NLCs) as promising carriers for cytotoxic drugs due to their potential to increase the solubility and bioavailability (BA) of poorly water-soluble and lipophilic drugs. The topical administration of anticancer drugs through NLCs has many advantages such as reduced side effects, reduce degradation, and enhanced penetration of the drug through the stratum corneum (SC) and thus increased drug targeting and therapeutics and also cost benefits. NLCs are composed of mixture of solid lipids and liquid lipids, because of that they have adequate capacity to accommodate large amount of drug as compared to SLN. Being lipid-based drug delivery systems, NLCs have been proved as better drug delivery carriers for cytotoxic drugs due to their potential to increase the solubility and BA of poorly water-soluble and lipophilic drugs. This review includes the applications and recent developments in topical drug delivery using NLCs. The structures, preparation techniques, modulation of drug release, long-term stability of NLCs and their physicochemical characterization are systematically described in this review. The potential of NLCs in the drug therapy of skin cancer has been highlighted.